Growth with endogenous technological change, banks and money. The case of an economy with innovative firms - Tirado Jiménez, Ramón (Estudios Económicos de El Colegio de México, 2000)
The aim of this paper is to expose and analyze a model of growth with endogenous technological change in an economy with banks and money. In growth theory there are not analyses drawing on the above lines. In this paper we provide some central results, relating the non-superneutrality of money with banking activity and its effects over the rate of growth that an innovative economy can reach. We show the cases of a risk neutral and a risk averse bank, and we conclude, by one hand, that the banking behavior plays a significative role on the long run rate of growth, because the agent is managing the individual savings, by the other hand, we describe that, actually, the monetary policy have influence on the long run development of the economy through the banking system.